DIPLOMATIC IMMUNITY AND OPPORTUNITIES - Ahmedov Azamjon; Soyibjonova Feruza Boxodirjon kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Diplomatic immunity is a universally recognized principle of international law that exempts diplomats from criminal jurisdiction and protects them from arrest and detention. This principle allows diplomats to perform their duties without fear of retribution or harassment. However, such immunity is not without limits, and diplomats can be expelled or prosecuted for certain crimes.